2023
DOI: 10.46799/ijssr.v3i9.521
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Company Growth and Liquidity on Company Value with Capital Structure as an Intervening Variable

Lydia Indah Permatasari,
Yanuar Ramadhan

Abstract: This study aims to obtain empirical evidence about the effect of company growth and liquidity on firm value, with capital structure as the intervening variable. The company's growth variable is measured using the percentage increase in the company's total sales, the difference between the company's total sales in this period and the previous period's total sales. The variable liquidity is measured by the current ratio, which is a measurement of the current assets owned by the company and the current liabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This suggests that management can effectively oversee existing assets to promote growth and generate profits, which in turn positively impacts firm value. However, contrary findings by Nugroho & Halik (2021) found that company growth had no impact on the firm value of insurance companies in Indonesia for the period of 2016-2020, nor for mining companies in Indonesia for the period of 2018-2022 (Permatasari & Ramadhan, 2023). It can be inferred that the company has struggled to effectively manage its assets resulting in a lack of profitability and, subsequently, no significant impact on the firm's value.…”
Section: Em-2024-6674mentioning
confidence: 72%
“…This suggests that management can effectively oversee existing assets to promote growth and generate profits, which in turn positively impacts firm value. However, contrary findings by Nugroho & Halik (2021) found that company growth had no impact on the firm value of insurance companies in Indonesia for the period of 2016-2020, nor for mining companies in Indonesia for the period of 2018-2022 (Permatasari & Ramadhan, 2023). It can be inferred that the company has struggled to effectively manage its assets resulting in a lack of profitability and, subsequently, no significant impact on the firm's value.…”
Section: Em-2024-6674mentioning
confidence: 72%